2020
DOI: 10.1080/23144599.2019.1708577
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-biochemical changes and prevalence of parasitic infections of indigenous chicken sold in markets of Kiambu County, Kenya

Abstract: This study aimed at determining parasitic prevalence and probable haemato-biochemical changes that may occur from parasitic infections in marketed indigenous chickens in Kiambu County, Kenya. Thirty adult chickens were purchased and examined for ectoparasites, haemoparasites and haemato-biochemical changes. Post mortem was conducted to recover gastrointestinal parasites and fecal samples taken for egg/oocyst counts. Forty-seven percent (14/30) of chickens examined were in poor body condition, 43% (13/30) in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Heterophils are engaged in phagocytosis against foreign bodies or dead tissues. Heterophils carry phagocytosis characteristics and become the frontier in fighting infectious diseases (Wamboi et al, 2020). The average percentage of eosinophils in this study was 3 ± 1.56% or within the normal range (2-8%).…”
Section: Total Leukocyte and White Blood Cell Differentialsupporting
confidence: 45%
See 1 more Smart Citation
“…Heterophils are engaged in phagocytosis against foreign bodies or dead tissues. Heterophils carry phagocytosis characteristics and become the frontier in fighting infectious diseases (Wamboi et al, 2020). The average percentage of eosinophils in this study was 3 ± 1.56% or within the normal range (2-8%).…”
Section: Total Leukocyte and White Blood Cell Differentialsupporting
confidence: 45%
“…Abun et al (2018) stated that total protein plasma is physiologically affected by age, hormone, growth, sex, nutrition intake, parasitic infection, and lost fluid in the body. Similarly, Wamboi et al, (2020) stated that the increase of the total protein plasma was found in chickens infected with Haemoproteus sp. Elagib et al, (2012) added that the concentration of protein plasma would decrease as the environmental temperature increased.…”
Section: Total Protein Plasma (Tpp) Blood Urea Nitrogen and Blood Alb...mentioning
confidence: 94%
“…These results are not surprising, and the most likely explanation would be due to scavenging activities and roaming habit of free-range and backyard chicken where the direct contact with excreta and soil and the noncommercial approach of owners would most likely include poor management including a lack of anthelminthic drug application ( Abdelqader et al., 2008 ; Abdullah and Mohammed, 2013 ). Furthermore, the free-range and backyard scavenging production system can play an important role in shedding helminth infections by contaminating the environment with parasite eggs and larvae ( Mwale and Masika, 2011 ; Wamboi et al., 2020 ). In contrast, birds housed in caged systems off the ground are largely separated from their excreta, disrupting the direct life cycle of the parasite which is reflected in the significantly lower average prevalence than backyard and free range ( Permin and Hansen, 1998 ; Permin et al., 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above figures, values of total protein and globulin recorded in this present study were higher and this is plausible as the birds were vaccinated late hence, they could have been exposed to natural infections. Infections in animals are accompanied by high serum total protein, elevated globulin and low albumin levels resulting from enhanced antibody secretion in response to infection (Orhue et al,2005;Wamboi et al, 2020). Coconut water supplementation seemingly reduced susceptibility of birds in groups B and C to infection probably as a result of its antimicrobial properties (Rajan et al, 2016;Rukmini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%